Concordar em discordar: análise discursivo-pragmática da polémica verbal em textos de opinião sobre o Acordo Ortográfico de 1990 - Ninitas, Mariana Silva (Revista da Associação Portuguesa de Linguística, 2021)
The main goal of this study is to analyze the construction of the polemical discourse, from a corpus composed by opinion texts concerning the Orthographic Agreement of 1990 (from now on OA90), taking into account the perspective of Discourse Analysis, Pragmatics, Rhetoric, Argumentation and Interactional Linguistics. The analysis of the corpus allows us to conclude that the speakers manipulate several strategies in the construction of their arguments, always with the intention of provoking and perpetuating the dissent.